ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA PEGAWAI SEKRETARIAT DEWAN PERWAKILAN RAKYAT DAERAH (DPRD) KABUPATEN CILACAP - Nurul Hasanah; Mutiasari Mutiasari; Sri Hartati (AmaNU: Jurnal Manajemen dan Ekonomi, 2021)
Work Discipline, and Work Environment on Employee Performance of the Secretariat of the Regional People's Representative Council (DPRD) Cilacap Regency. The sample in this study were 44 respondents using the census method. The analytical tool used is Multiple Linear Regression Analysis and t test. The results of the analysis are as follows: Partially education has a significant influence on the performance of the employees of the Cilacap Regional Representative Council Secretariat (DPRD), this is evidenced by the t-count value of education (t-count X1) which is greater than t-table (2.386> 2.021). Work discipline partially has a significant effect on the performance of the employees of the Regional Representative Council Secretariat (DPRD) of Cilacap Regency, this is evidenced by the t-count value of work discipline (t-count X2) which is greater than t-table (2,371> 2,021). The work environment partially has a significant influence on the performance of the employees of the Regional Representative Council Secretariat (DPRD) of Cilacap Regency, this is evidenced by the t-count value of the work environment (t-count X3) which is greater than t-table (3.175> 2.021).